2017
DOI: 10.1016/j.elecom.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Submicromolar quantification of pyocyanin in complex biological fluids using pad-printed carbon electrodes

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Pseudomonas aeruginosa is a Gram-negative bacteria and human pathogen that is responsible for a high number of hospital infections and is prevalent in patients with compromised immune systems, chronic wounds, and in the lungs of those suffering from cystic fibrosis. , Several redox-active phenazine derivatives 2-alkyl-4-quinolones (AHQs) have been identified that behave as QS molecules produced by P. aeruginosa, e.g., 4-hydroxy-2-heptylquinoline (HHQ) and 2-heptyl-3,4-dihydroxyquinoline (pseudomonas quinolone signal, PQS), see Figure for chemical structures. ,,,, AHQs exist in another tautomeric form and can also be termed 4-hydroxy-2-alkylquinolines (HAQs) . The neutral 4-quinolone rather than the 4-hydroxy-quinoline is the predominant species in the pH range 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a Gram-negative bacteria and human pathogen that is responsible for a high number of hospital infections and is prevalent in patients with compromised immune systems, chronic wounds, and in the lungs of those suffering from cystic fibrosis. , Several redox-active phenazine derivatives 2-alkyl-4-quinolones (AHQs) have been identified that behave as QS molecules produced by P. aeruginosa, e.g., 4-hydroxy-2-heptylquinoline (HHQ) and 2-heptyl-3,4-dihydroxyquinoline (pseudomonas quinolone signal, PQS), see Figure for chemical structures. ,,,, AHQs exist in another tautomeric form and can also be termed 4-hydroxy-2-alkylquinolines (HAQs) . The neutral 4-quinolone rather than the 4-hydroxy-quinoline is the predominant species in the pH range 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…This setup could regenerate reductive pyocyanin from its oxidative state and this way enable repeated pyocyanin registration. With this method it was possible to reach an LOD of 47 pM [ 43 ].…”
Section: Electrochemical Detection Of Pyocyaninmentioning
confidence: 99%
“…To successfully apply the electrochemical detection of pyocyanin for PA identification in clinical samples, several studies measured human fluids spiked with pyocyanin [ 31 , 32 , 48 ]. The investigated human fluids covered urine, blood, bronchial lavage, sputum, saliva and hypertonic saline for laryngeal aspirate suctions as well as simulated wound fluid and artificial sputum medium [ 25 , 33 , 37 , 42 , 43 ]. PA is a urinary tract pathogen, which makes urine an obvious body fluid to develop pyocyanin detection in.…”
Section: Towards Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have demonstrated applications of the PADs to different types of food and environmental samples using detection schemes such as colorimetry, electrochemistry, fluorometry, and chemiluminescence. Colorimetry is the most frequently employed detection method because it is simple to achieve qualitative and quantitative analyses of analytes by observing the color change in the detection zones on the PAD. The color images are captured with a digital camera, smartphone, or scanner, which then is followed by image processing using software such as ImageJ. , …”
Section: Introductionmentioning
confidence: 99%